The association of Intron 4 VNTR and Glu298Asp polymorphisms of the nitric oxide synthetase 3 gene and vasculogenic erectile dysfunction in Turkish men - AKDENİZ, ESRA (TAYLOR & FRANCIS INC, 2019)
Several studies have focused on the impaired role of endothelial nitric oxide synthase (NOS3) gene polymorphism and its association to erectile dysfunction (ED). However, currently controversial results have been reported due to their significant heterogeneity. The present study aimed to assess the genotypic distribution and the allelic frequency of Intron 4 VNTR and Glu298Asp gene polymorphisms in vasculogenic ED patients compared to healthy controls of a specific region of Turkey. A total of 75 patients with ED (median age: 56, IQR:10.5) and 75 healthy controls (median age: 56, IQR:10.5) were prospectively analyzed. All subjects were equally evaluated by the same physician with detailed history-taking, physical examination, International Index of Erectile Function (IIEF) questionnaire, and blood tests (incl. glucose, testosterone, triglyceride and total cholesterol level). Those with an IIEF score under 26 were considered to have ED, by classifying them according to their scores as mild (22-25), moderate (11-21) and severe (1-10) ED. Color doppler ultrasonography was carried out in patients with an IIEF score <22. Hypertension, diabetes mellitus, coronary artery disease, and smoking status were significantly associated with the ED group compared to control subjects with p values of <0.001, <0.001, 0.002 and <0.001, respectively. Overall genotype frequencies was 47 (31%) a/a, 22 (15%) a/b, 82 (55%) b/b for Intron 4 VNTR and 56 (37%) GG, 78 (52%) GT, 16 (11%) TT for the Glu298Asp polymorphism. The frequencies of Intron 4 VNTR a/a allele and Glu298Asp GT allele were associated with severe ED, while a/b and TT were associated with moderate or mild, and b/b and GG were associated with no ED. In contrast to Glu298Asp, statistically significant differences in genotypic frequencies of Intron 4 VNTR gene polymorphism between ED and control subjects was established.
Keywords: Erectile dysfunction; eNOS; gene polymorphism; CORONARY-ARTERY-DISEASE; ENOS GENE; G894T POLYMORPHISMS; SYNTHASE GENE; RISK-FACTOR; SILDENAFIL; T-786C; I/D